ANALYSIS OF THE DIFFICULTIES OF CLASS X STUDENTS OF SMKN 4 PALANGKA RAYA IN SOLVING TRIGONOMETRY PROBLEMS - Desti Haryani; Ardo Subagjo; Muhamad Hamdani; Qodri Ali Hasan; Novie Widyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2022)
This research was motivated by the low scores obtained by students in the trigonometry material for the area of ​​triangles in class X GP of SMK Negeri 4 Palangka Raya. In the 2019/2020 school year, only 48% of the 34 students achieved the school's Minimum Completeness Criteria, which is 65. The purpose of this study is to describe the difficulties experienced by students in solving math problems on trigonometry material and the factors that students experience difficulties. This research is a qualitative descriptive study. The results showed that the difficulties experienced by students in solving trigonometry problems were: (a) Difficulties in counting were difficulties in performing number operations. The factor that causes students to be less careful. (b) Difficulty in transferring knowledge, namely determining the formula and sine value. The reason is that students do not understand the material being taught so they cannot distinguish the formula used in determining the area of ​​a triangle according to what is known in the problem. (c) Difficulty in understanding mathematical language, namely understanding mathematical symbols correctly. The reason is that students are less careful in writing down the numbers that match the existing mathematical symbols. (d) Difficulty in visual perception, namely making and understanding sketches or drawings based on existing problems. The reason is that students do not understand how to change what is asked in the question of the shape of a triangular image and vice versa.